Combined pharmacological activation of AMPK and PPARδ potentiates the effects of exercise in trained mice. Issue 5 (20th March 2016) - Manio, Mark Christian C.; Inoue, Kazuo; Fujitani, Mina; Matsumura, Shigenobu; Fushiki, Tohru
Abstract: The combined activation of the cellular energy sensor AMP‐activated protein kinase (AMPK) and the nuclear transcription factor peroxisome proliferator‐activated receptor delta (PPAR δ ) has been demonstrated to improve endurance and muscle function by mimicking the effects of exercise training. However, their combined pharmacological activation with exercise training has not been explored. Balb/c mice were trained on a treadmill and administered both the AMPK activator AICAR and the PPAR δ agonist GW0742 for 4 weeks. AICAR treatment potentiated endurance, but the combination of AICAR and GW0742 further potentiated endurance and increased all running parameters significantly relative to exercised and nonexercised groups (138–179% and 355% increase in running time, respectively). Despite the lack of change in basal whole‐body metabolism, a significant shift to fat as the main energy source with a decline in carbohydrate utilization was observed upon indirect calorimetry analysis at the period near exhaustion. Increased energy substrates before exercise, and elevated muscle nonesterified fatty acids (NEFA) and elevated muscle glycogen at exhaustion were observed together with increased PDK4 mRNA expression. Citrate synthase activity was elevated in AICAR‐treated groups, while PGC‐1 α protein level tended to be increased in GW0742‐treated groups. At exhaustion, Pgc1a was robustly upregulated together with Pdk4, Cd36, and Lpl in the muscle. A robust upregulation of Pgc1a and a downregulation in Chrebp were observed in the liver. Our data show that combined pharmacological activation of AMPK and PPAR δ potentiates endurance in trained mice by transcriptional changes in muscle and liver, increased available energy substrates, delayed hypoglycemia through glycogen sparing accompanied by increased NEFA availability, and improved substrate shift from carbohydrate to fat. Abstract : AMPK and PPARδ activators have been termed "exercise mimetics" because of the shared effects with exercise training on skeletal muscle. However, their utilization in combination with exercise training has not been investigated. Our findings demonstrate that AMPK activation potentiates endurance which was further potentiated together with PPARδ agonism in trained mice. This was accompanied by enhanced substrate supply, shift in primary fuel, transcriptional regulation of metabolic genes in both muscle and liver, and increased mitochondrial density.